THE SEARCH FOR GENE MUTATIONS AT CYSTIC FIBROSIS IN CHILDREN BY THE METHOD OF HIGH-RESOLUTION MELTING ANALYSIS - M. Y. Donnikov; V. V. Meshcheryakov (Сибирский научный медицинский журнал, 2019)
High-resolution melting analysis (HRMA) is promising for preliminary scanning of the nucleotide sequence of the cystic fibrosis transmembrane conductance regulator gene ( CFTR ), which mutations are responsible for the development of cystic fibrosis. In Russia this method has not yet found practical application. The aim of this work was the analysis of the efficiency of the HRMA method at the first stage of molecular diagnostics of cystic fibrosis in children. Materials and methods. In order to validate the new technique for extended molecular genetic analysis we examined 43 control DNA samples obtained from children with confirmed cystic fibrosis diagnosis and known CFTR mutations. Results. The specificity of cystic fibrosis molecular diagnostics with the implementation of the HRMA method was 100 %, the sensitivity was 97.3 %. In two samples with extended heterozygous deletion of the 2nd and 3rd exons melting patterns were identical to the wild type ones. Conclusions. The high efficiency of the HRMA method proves the possibility of its usefulness in clinical practice at the first stage of cystic fibrosis molecular diagnostics in children toward the reduction of the diagnostic search duration. In most cases this method allows to determine CFTR gene mutation type. Long deletions/insertions and complex heterozygous restructurings still cannot be detected using HRMA. Multiplex ligation-dependent probe amplification is required to determine this mutation type.